The king's trial : - Jordan, David P. (University of California Press, 1981)
On August 10, 1792, Louis XVI of France abandoned his Paris chateau, walked across the Tuileries gardens, and surrendered his crown. In the tumultuous months that followed, he was tried, found guilty, and sent to the guillotine. When originally published, David Jordan's riveting account of that turbulent time identified key issues, focused attention on a matter once considered only an episode of French history, and reframed the academic debate on the meaning of the most significant trial in French history. His new preface considers the scholarship of the past twenty-five years and places The King's Trial in the current context.